Stakeholder Perceptions in a No Smoking Area Public Campaign in Bima City - Zahratul Hayati; Bambang Irawan (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to identify and understand the efforts of stakeholders in implementing a no-smoking area policy in Bima City. This study uses a qualitative descriptive method using the theory of Health belief model. Data collection techniques were carried out by means of interviews and observations. Checking the validity of the data is done by triangulation method. The data analysis process includes data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that the role of stakeholders is still lacking in implementing the no-smoking area policy in Bima City. However, the implementation of the policy is not supported by the commitment of the policy implementers so that the role of stakeholders in implementing the no-smoking area policy in Bima City still has to be re-evaluated.